A study of the artistic corpus of red cave paintings in El Buxu cave (Cangas de Onís, Asturias, Spain). (October 2022) - García-Alonso, Beatriz; Menéndez Fernández, Mario; Pérez-Diez, Silvia; Maguregui, Maite
Highlights: The corpus of red paintings at the Buxu Cave (Cangas de Onís, Asturias, Spain) has been defined with two signs, a zoomorph, finger dots, linear strokes, some undefined marks and regular spots. The studies revealed a new definition of a zoomorphic figure in the Buxu Cave as a deer or a reindeer. Elemental analysis was performed on series of red pigment and ochre samples, recovered from various strata, using X-ray fluorescence, while uncovering potential chemical links among the samples. Stratigraphic analysis of some of the red paintings has revealed an overlapping by Solutrean and Magdalenian engravings and black paintings onto the red remains, showing they are the oldest artistic evidences inside the cave. The stratigraphic studies of the paintings, and the parallels proposed for some of them, place them in a pre-Magdalenian artistic period. Abstract: El Buxu cave, which is located in the village of Cardes (Cangas de Onís, Asturias), has been studied since the 1980s, with multiple excavations taking place inside the cave. This work has uncovered a complete artistic corpus, marking out several phases of occupation, with paintings dating to the first phases of the Upper Palaeolithic, Solutrean and Lower and Middle Magdalenian periods. This paper presents a new review of its rock art, documenting all of the red paintings inside the cave, most of which have never been published up until this point. The most notable inclusion is the new description of a zoomorphic figure painted in red, which has previously been interpreted as an aurochs, but whose features are in fact closer to those of a deer or reindeer. In addition, stratigraphic analysis of some of the paintings has revealed that they are overlapped by Solutrean and Magdalenian engravings and black paintings inside the cave. Elemental analysis was performed on series of red pigments and ochre samples, recovered from various strata using X-ray fluorescence spectroscopy. The resulting dataset was treated using Principal Component Analysis, providing a deeper understanding of the composition of the rock art in El Buxu cave, while uncovering potential correlations between the samples according to their elemental composition. After comparing additional evidences from other red cave paintings in the region with the red pictographs in the cave, along with the stratification of paint pigments and their relationship with the ochre samples in each stratum, it appears that the red paintings comprise the oldest group of pictures inside the cave and can be broadly dated to the pre-Magdalenian cultural period.